A comparative study on nursing students' attitudes towards death and palliative care before and after their clinical internship in China - Ju, Qingmei; Liu, Yang; Soh, Kim Lam; Guo, Yiqiang (Wolters Kluwer Health, 2026)
BACKGROUND: Nurses play a central role in delivering palliative care (PC), and their attitudes toward death directly affect the quality of care provided. Clinical internships represent a critical transition for nursing students, bridging theoretical knowledge and practical experience, and shaping their development as professional caregivers. However, research in this area remains limited. This study aims to understand the changes in attitudes towards death and PC among nursing undergraduate students before and after clinical internships in China. METHODS: A longitudinal survey was conducted with 224 nursing undergraduate students from a medical college selected as the study participants. The Chinese version of the Death Attitude Profile-Revised, Frommelt Attitude Toward Care of the Dying Scale, and the Palliative Care Competence Self-Assessment Questionnaire were used for the survey. RESULTS: After the internship, nursing students' scores for death fear, death anxiety, avoidance acceptance, and approach acceptance attitudes were higher than before the internship; the score for natural acceptance attitude was lower than before the internship. The total score of the PC competence after the internship (100.60 ± 9.80) was lower than before the internship (103.74 ± 7.75), and the differences were statistically significant. The self-assessed competence percentages for various items of PC ranged from 31.8% to 50.5%, all lower than before the internship. CONCLUSION: Clinical practice poses real challenges to nursing students, resulting in a decline in positive attitudes towards death and PC competence. It is necessary to optimize clinical teaching on PC, address existing deficiencies, enhance nursing students' positive attitudes towards death and PC competence, and ensure the adequacy and stability of the PC workforce.